Driving Priorities in Risk‐based Regulation: What's the Problem?. (3rd November 2016) - Baldwin, Robert; Black, Julia
Abstract : Both risk‐based and problem‐centred regulatory techniques emphasize giving priority to matters that are serious and important. In the case of both risks and problems, however, issues of identification, selection, and prioritization involve inescapably normative and political choices. It is important, therefore, to understand why regulators target the risks and problems that they do; which factors drive such choices; and how regulation is affected when these factors pull in similar or opposite directions. Such an understanding provides a fresh framework for thinking about the challenges of both risk‐based and problem‐centred regulation. The analysis presented here does not oppose either risk‐based or problem‐centred regulation, but it illustrates why neither is as straightforward as simple calls for 'better regulation' may suggest, and it proposes ways in which key aspects of those challenges may be addressed.